PENGEMBANGAN BUKU CERITA BERGAMBAR BILINGUAL PADA SISWA SEKOLAH DASAR - Regita Halid; Rusmin Husain; Fidyawati Monoarfa; Wiwy Triyanty Pulukadang; Sukri Katili (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The formulation of the problem in this research is the initial learning conditions by using bilingual picture storybooks at SDN (State Elementary School) 2 Limboto Barat, how to develop bilingual picture storybooks for grade IV students of SDN 2 Limboto Barat, and the feasibility of bilingual picture storybooks for grade IV students of SDN 2 Limboto Barat. This research aims to describe the initial learning conditions using bilingual picture storybooks at SDN 2 Limboto Barat, develop bilingual picture storybooks for grade IV students of SDN 2 Limboto Barat, and describe the feasibility of bilingual picture storybooks for grade IV students of SDN 2 Limboto Barat. The method used is a development research method that uses the Thiagarajan (1974) model design, the 4D model, which consists of 4 stages: defining, designing, developing, and disseminating. The research findings demonstrated that the development of bilingual picture storybooks based on media expert validation obtained a percentage of 96% (very feasible), linguist validation obtained a percentage of 88% (very feasible), practitioner expert validation in terms of language and media obtained a percentage of 100% (very feasible). This validation obtained an average percentage of 96% (very feasible). Based on the findings, it can be concluded that the development of bilingual picture storybooks is very feasible to use in the learning process.